Testing of MSME Financial Performance Model in Indonesia with Financial Technology Moderation and Green Innovation Towards Advanced Indonesia - Tandry Whittleliang Hakki; Merna Surjadi; Jocelyn Jocelyn (Dinasti Publisher, 2024)
Medium enterprises are a fairly important part of the business sector in playing a real role in various economic interests in national development, especially for the creation of businesses and jobs, especially after the Covid-19 pandemic in 2023. This is supported by the Ministry of Tourism and Creative Economy, which was stated by the Minister of Tourism and Creative Economy/Head of the Tourism and Creative Economy Agency, Mr. Sandiaga Salahuddin Uno, who said that tourism and creative economy actors, especially in the MSME sector, must continue to hone their digital technology skills to boost the economy and create jobs. Based on this phenomenon, researchers are interested in researching digital technology and green innovation in the MSME sector in Indonesia. This study aims to analyze the influence of Strategic Management Accounting, MSME Digitalization, and Leadership Quality on MSME Financial Performance. Where in this study, Financial Technology and Green Innovation, which are supporting factors in addition to advances in information technology, are used as moderating variables between the variables: Strategic Management Accounting, MSME Digitalization, and Leadership Quality on MSME Financial Performance. This study uses primary data conducted by distributing questionnaires to Micro, Small, and Medium Enterprises in several major cities in Indonesia, such as the target of this study, namely MSMEs in the cities of Jakarta, Denpasar, Bandung, Surabaya and Medan. The results of the study indicate that MSME Digitalization and Leadership Quality have a significant effect on MSME financial performance, but Strategic Management Accounting does not have a significant effect on MSME financial performance. Financial Technology strengthens the influence of MSME Digitalization and leadership quality on MSME financial performance but Financial Technology does not strengthen Strategic Management Accounting on MSME financial performance. Green innovation strengthens the influence of MSME digitalization on MSME financial performance but Green innovation does not strengthen the influence of Strategic Management Accounting and Leadership Quality on MSME Financial Performance